The changing landscape of hepatitis C virus therapy: focus on interferon-free treatment. (September 2015) - Lam, Brian P.; Jeffers, Thomas; Younoszai, Zahra; Fazel, Yousef; Younossi, Zobair M.
Chronic hepatitis C (CHC) affects over 185 million individuals worldwide, approximately 3% of the world's population. CHC can lead to quality of life impairment, cirrhosis, hepatocellular carcinoma (HCC), liver failure and liver-related death. While CHC has been associated with increases in HCC, liver-related mortality and all-cause mortality, being cured of CHC is associated with improvement in these outcomes. Older interferon-based regimens were complex and toxic and required 6–12 months of therapy, with cure rates averaging around 40–45% for HCV genotype 1. Newer interferon-free regimens are now available in the US, Europe, Japan and in other countries. These regimens have short durations, minimal side effects, low pill burden and efficacy approaching 90–100%. We may eventually see single-tablet regimens lasting no more than 4–6 weeks. This review will summarize the data regarding these interferon-free regimens, including Gilead's Harvoni (sofosbuvir/ledipasvir), AbbVie's Viekira Pak (paritaprevir/ritonavir/ombitasvir with dasabuvir), and Janssen's Olysio (simeprevir) with sofosbuvir. Some practical considerations as we move into an interferon-free era will also be discussed, such as patient adherence and drug–drug interactions.